Assess the Anti-Inflammatory and Analgesic Activity of Leaves of Raphanus Sativus – An In Vivo Design - Manisha, Devi; Rashi, Karnati Naga; Harini, Kapilavai; Boggula, Narender; Bakshi, Vasudha; Sayeed, Mohammed (Asian Journal of Pharmaceutical Research and Development, 2020)
Background: Natural products found from plants have been conveying a vital role among human being since ancient times. An enormous number of scientific reports evidenced of using the medicinal plants as natural remedies. Nowadays, the medicinal plant is using as an alternative medicine to synthetic drugs. The use of medicinal plants singly or in combination in treating different ailments has been practiced by traditional medical healers for a very long time. People of Mesoamerica have utilized plants and products from plants in curing and relieving ailments for centuries. Aim: The present aim of the study is to assess the anti-inflammatory and analgesic activity of Ethanolic Extract of leaves of Raphanus sativus (EERS) on animal models and therefore to determine the scientific basis for its use in traditional medicine in the management of anti-inflammatory condition. Methods: Anti-inflammatory activity was evaluated using carrageenan and histamine-induced paw edema methods. Analgesic activity of Ethanolic Extract of leaves of Raphanus sativus (EERS) was estimated against a hot plate, acetic acid induced writhing and formalin tests. Results: The extracts showed significant anti-inflammatory and analgesic activities with a dose-dependent manner. Anti-inflammatory activity of olive tree extract at 250 and 500mg/kg doses was more important compared to the used standard drugs (p<0.05), in both carrageenan and histamine-induced paw edema tests. In analgesic assays, results showed that 500mg/kg dose of olive tree extract has a significant analgesic effect through both peripheral and central mechanisms. Conclusion: This study provided evidence on the traditionally claimed uses of the plant in pain and inflammatory diseases, and Raphanus sativus could be potential source for development of new analgesic and anti-inflammatory drugs.